Partial Substitution of Barley Malt by Wheat Bran in the Grist Results in Lager Beer with Better Taste Profile and Higher Content in Arabinoxylan-Oligosaccharides (AXOS) - Veraverbeke, Wim S.; De Cock, Jan; De Rouck, Gert; Delcour, Jan A.; Van Mellaert, Herman; Aerts, Guido; Broekaert, Willem F. (BrewingScience, 2011)
The use of wheat bran as a new adjunct in brewing at 25 % of total grist in combination with the use of a xylanase in the mashing step was tested by brewing control and bran-brewed lager beers. Sensory analysis revealed marked improvements in taste profile due to bran-brewing, with statistically significant increase in body, smoothness and warming notes, and a decrease in acetaldehyde, after-bitterness, drying and grainy attributes. A detailed physico-chemical analysis of the beers was performed. Key parameters on which a significant impact was demonstrated include increased content of arabinoxylanoligosaccharides (AXOS), ferulic acid, and soluble protein, and lowered content of aldehydes, the latter indicative of reduced oxidation during brewing. Traditional but long forgotten use of wheat bran for brewing of small beers holds potential to make innovative beers with an interesting taste profile.